Genre-Based Inquiry of Literature Review in Social Sciences Master’s Theses - Sumayo, Gideon; Tulud, Donnie (International Journal of Language and Literary Studies, 2021)
Literature review (LR) as a distinct type of genre was disregarded continuously, and its rhetorical moves and steps were less explored. Hence, this research attempted to study the rhetorical structure through move analysis of the LR section of social science master’s theses. The research determined the common rhetorical moves employed in the 30 LR sections of quantitative theses at the University of Southern Mindanao Graduate School. The rhetorical structure in the LR sections was examined using the move structure model formulated by Hsiao and Yu (2012). Results revealed that the thirty LR corpora employed presenting field knowledge, occupying the niche, but deficient in classifying themes, and integrating and relating previous works to the current study as their text features. Findings also revealed that every thesis writer in the 30 LR corpora have various ways of presenting their LRs, which means that there is no general pattern or format in writing LR in thesis manuscripts analyzed. This implies that the LRs in the master’s theses analyzed are written in a variety of styles depending on the orientation of the writers not following Hsiao and Yu’s prescribed model. Also, an additional step was subsumed under Move 4 and is labeled announcing the conceptual framework, which is not evident in the previously published model structure for LR, which means this step is considered a new structure in the literature review section evident only in the USM Graduate School.